Integration of Corporate Governance and Social as a Catalyst for Islamic Banking Financial Performance; Evidence in Indonesia - Sri Anugrah Natalina; Grahita Chandrarin; Maxion Sumtaxy; Rofik Efendi; Yuliani; Dijan Novia Saka (PT FORMOSA CENDEKIA GLOBAL, 2024)
Corporate governance can be assessed from how the company has been run openly and transparently, to gain public trust in market mechanisms. Islamic banking in Indonesia shows a pattern that social activities are an obligation that must be carried out. Social is a characteristic of Indonesian banking, a financial institution that has implemented the concept of sharia. In this study, the sample used amounted to 132 data on BUS's financial statements for 11 years from 2010-2020. As a result, improved governance, actually led to a decline in financial performance, by the regression value of -0.1682. Meanwhile, the social variable shows that if social performance increases, financial performance also increases by 0.282.